2007
DOI: 10.1111/j.1440-1843.2007.01075.x
|View full text |Cite
|
Sign up to set email alerts
|

Gender‐associated differences in dyspnoea and health‐related quality of life in patients with chronic obstructive pulmonary disease

Abstract: Gender differences exist in dyspnoea and HRQoL in patients with COPD. These need to be considered when designing treatment strategies for COPD patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
38
3
2

Year Published

2010
2010
2024
2024

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 60 publications
(50 citation statements)
references
References 34 publications
7
38
3
2
Order By: Relevance
“…The finding that HRQL is worse in women is consistent with previous studies of using other HRQL instruments (3)(4)(5). Do factors determining quality of life in men and women differ; with mental state and symptoms playing a more dominant role in HRQL among women with COPD (42)?…”
Section: Discussionsupporting
confidence: 86%
See 1 more Smart Citation
“…The finding that HRQL is worse in women is consistent with previous studies of using other HRQL instruments (3)(4)(5). Do factors determining quality of life in men and women differ; with mental state and symptoms playing a more dominant role in HRQL among women with COPD (42)?…”
Section: Discussionsupporting
confidence: 86%
“…Previous studies have shown that HRQL in COPD is influenced by low physical capacity, a high level of dyspnoea and worsening of emotional state, but it is also associated with female sex, reduced lung function, older age, a history of heavy tobacco use and frequent exacerbations (3)(4)(5)(6)(7)(8)(9)(10)(11)(12).…”
Section: Introductionmentioning
confidence: 99%
“…20). Patient-based studies also indicate that women with cardiopulmonary conditions have greater respiratory symptoms and exercise intolerance compared to men (120,267). The mechanisms underlying the perception of breathlessness remain unclear, and how sex-based differences in sensory input modulate the dyspnea sensations are unknown.…”
Section: The Healthy Older Femalementioning
confidence: 93%
“…This is an unexpected result because the association between lung function and HRQL is considered to be weak. 38,39 Since female COPD patients tend to report a lower HRQL than males 40 and the psychological distress in COPD patients is found to be associated with HRQL, 41 one might have expected stronger influence from gender, anxiety and depression in the regression model. Our result, however, suggests that a lung function above a certain level may be crucial in order to deal with symptoms, perform physical activities and reduce the psychosocial strains of the disease.…”
Section: Discussionmentioning
confidence: 99%